1969
DOI: 10.2307/1936264
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes in Swine Associated with Environmental Temperature

Abstract: Ten animals from two litters of English large white pigs were weaned at 12—15 days of age and placed one per cage within constant—temperature rooms. In the first group, a comparison was made between three animals raised at 5°C and their littermates raised at 35°C. There were marked differences in appearance and in gross morphology. Those from the cold environment had more hair, were shorter and more stocky, and had a shorter tail and smaller ears than their littermates. A second group of animals were raised at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
62
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 13 publications
6
62
0
Order By: Relevance
“…There is developmental plasticity in mammalian body proportions as a result of thermal stress (30,34). Yet, among at least recent human immigrant groups displaced to different environments, there is little change in body proportions, even over a number of millennia (23).…”
Section: Discussionmentioning
confidence: 99%
“…There is developmental plasticity in mammalian body proportions as a result of thermal stress (30,34). Yet, among at least recent human immigrant groups displaced to different environments, there is little change in body proportions, even over a number of millennia (23).…”
Section: Discussionmentioning
confidence: 99%
“…Sumner (1909) was the first of many biologists to report an "Allen-type effect" after rearing laboratory mice at cold and warm temperatures throughout their active growth period (Sumner, 1909). Others have confirmed this basic observation in various species, including rats (Chevillard et al, 1963;Lee et al, 1969;Riesenfeld, 1973;Steegmann, 2007), mice (Sundstroem, 1922;Ogle, 1934;Ashoub, 1958;Harland, 1960;Barnett and Scott, 1963;Harrison, 1963;Noel and Wright, 1970), rabbits (Ogle and Mills, 1933), and pigs (Weaver and Ingram, 1969). The consistent result among these studies is that animals reared in cold conditions have shorter ears, limbs, and tails, while those raised at warmer temperatures have extremities that are lengthened in a gradient fashion with increasing temperature.…”
mentioning
confidence: 93%
“…These studies, however, have not examined the possible effects of cold temperature exposure on morphological adaptations which may serve to reduce the degree of environmental stress experienced. Pronounced morphological adaptations to cold are considered to be genetically controlled but studies by Weaver and Ingram (1969) and Heath and Ingram (1979) have shown that a relatively short-term exposure of growing pigs to a cold environment can result in marked alterations in development.…”
mentioning
confidence: 99%